Self-Directed Learning: A Tool for Lifelong Learning. (April 2014) - Boyer, Stefanie L.; Edmondson, Diane R.; Artis, Andrew B.; Fleming, David
A meta-analytic review of self-directed learning (SDL) research over 30 years, five countries, and across multiple academic disciplines is used to explore its relationships with five key nomologically related constructs for effective workplace learning. The meta-analysis revealed positive relationships between SDL and internal locus of control, motivation, performance, self-efficacy, and support. The use of an actual SDL project in an undergraduate sales management course and an MBA selling and sales management course is used to provide supporting evidence and practical advice for educators seeking to use SDL to promote lifelong learning skills in students.